Power fluctuation suppression for grid connected permanent magnet synchronous generator type wind power generation system - Nid, A.; Sayah, S.; Zebar, A. (Національний технічний університет "Харківський політехнічний інститут", 2024)
Weather changes lead to create oscillations in values of power extracted from renewable energy resources (RERs). These power oscillations pose significant challenges in RERs integration process with the power grid systems, through its effects on power system stability. Many studies have been performed in various methods to mitigate the output power fluctuation of wind power generation system (WPGS). Purpose. This study focuses on increasing the mitigation rate of the output power fluctuation of WPGS caused by the rapid wind speed changes during wind gusts. Superconducting magnetic energy storage (SMES) system through its properties represents an effective solution for the WPGS power fluctuation issue. WPGS and SMES systems are linked to power grid system through the point of common coupling (PCC). Methods. This paper proposes two robust controllers for controlling the SMES system. The first controller is a Fuzzy Logic Controller (FLC), which has been utilized for controlling the power exchange between the SMES coil and the PCC of the utility grid. While the second controller is a PI controller, which have been utilized to regulate the voltages between the two sides of the PCC and the DC link capacitor in the SMES system. The proposed controllers have been constructed so that can make the SMES system absorb/deliver the real power instantaneously from/toward PCC according the wind speed changes. MATLAB/Simulink has been utilized to simulate the system under study and test the performance of proposed controllers. In addition, two different wind speed scenarios have been used in the simulation. Practical value. Results of simulation have proven the effectiveness of proposed controllers so that the active power fluctuation delivered to utility grid can be reduced by up to 89 %.

Зміни погоди призводять до коливань значень потужності, що надходять з відновлюваних джерел енергії (RERs). Ці коливання потужності створюють серйозні проблеми у процесі інтеграції RERs з енергосистемами через їх вплив на стабільність енергосистеми. Було проведено велику кількість досліджень різних методів пом’якшення коливань вихідної потужності системи вітрогенерації (WPGS). Мета. Це дослідження спрямоване на підвищення ступеня пом’якшення коливань вихідної потужності WPGS, викликаних швидкими змінами швидкості вітру під час поривів вітру. Система надпровідного накопичення магнітної енергії (SMES) завдяки своїм властивостям є ефективним вирішенням проблеми коливань потужності WPGS. Системи WPGS та SMES пов’язані з енергосистемою через точку загального підключення (PCC). Методи. У цій статті пропонуються два робастні контролери для управління системою SMES. Перший контролер є контролером нечіткої логіки (FLC), який використовувався для управління обміном енергії між котушкою SMES і PCC енергосистеми. У той час як другий контролер є ПІ-регулятором, який використовувався для регулювання напруг між двома сторонами PCC і конденсатором кола постійного струму в системі SMES. Пропоновані контролери були сконструйовані таким чином, щоб система SMES могла миттєво поглинати/передавати реальну потужність від/до PCC відповідно до змін швидкості вітру. MATLAB/Simulink використовувався для моделювання досліджуваної системи та перевірки продуктивності пропонованих контролерів. Крім того, при моделюванні використовувалися два різні сценарії швидкості вітру. Практична цінність. Результати моделювання довели ефективність пропонованих контролерів, що дозволяють знизити до 89 % коливання активної потужності, що подається до енергосистеми.
Keywords: wind power generation system; power grid system; superconducting magnetic energy storage; fuzzy logic control; вітроенергетична система; система електромережі; надпровідний магнітний накопичувач енергії; керування на нечіткій логіці